Treatment Of The Two Class Iı Cases Wıth Mars And Acrylıc Splınt Mars Applıance - Müyesser Saraç; Didem Dalaman Güner (Galenos Yayinevi, 1995)
Treatment changes of the two skeletal and dental class II cases treated with variations of the Herbst appliance-Mars and Acrylic splint Mars appliance-have been investigated in order to examine treatment changes, cephaometric and "CLII correction analysis" are carried out. At the end of the four mounths treatment period intermaksilleary relation, soft tissue profile, overjet and distal molar relation have been improved. In the treatment of the high angle case, S-N/Go-Me angle did not change. Neuromuscular adaptation and vertical cuspal interdigitation must be achived with activator in retention period for stabilization of the skeletal and dental improvement obtained in a short treatment period.